Implikasi Kepemimpinan Kristen Berdasarkan Kitab Hakim-Hakim 19:1-30 - Selatieli Sihura; Agus Santoso; Marthin Steven Lumingkewas (Sekolah Tinggi Teologi Torsina Surakarta, 2022)
Leadership in the Bible is essential, and the election seems based on character and morals. This is also a fundamental problem in Judges 19:1-30 where there is a problem with the character and immorality of the Israelite leader. This article aims to explain Judges 19:1-30 and provide implications for Christian leadership. The method used is a historical criticism of the study of biblical theology analysis. The results of this study are a Christian leader who serves with a heart, recognizes the need for service, is spiritually sound, oriented to the congregation, has education for servants, and education for the congregation.AbstrakKepemimpinan dalam Alkitab sangat penting dan agaknya pemilihan itu didasarkan kepada karakter dan moral. Hal ini juga menjadi permasalahan tersirat di Hakim-Hakim 19:1-30 dimana muncul permasalahan karakter dan amoral dari pemimpin Israel. Artikel ini bertujuan menjelaskan Hakim-Hakim 19:1-30 dan memberikan implikasi pada kepemimpinan Kristen. Metode yang digunakan adalah historis kritis pada kajian analisis teologi biblika. Hasil penelitian ini adalah seorang pemimpin Kristen memiliki melayani dengan hati, mengenali kebutuhan pelayanan, spiritual yang baik, berorientasi pada jemaat, pendidikan bagi para pelayan, dan pendidikan bagi jemaat.